Exoskeleton gait training on real-world terrain improves spatiotemporal performance in cerebral palsy - Tagoe, Emmanuella A.; Fang, Ying; Williams, Jack R.; Stone, Julie L.; Lerner, Zachary F. (Frontiers in Bioengineering and Biotechnology, 2024)
Walking is essential for daily life but poses a significant challenge for many individuals with neurological conditions like cerebral palsy (CP), the leading cause of childhood walking disability. While lower limb exoskeletons show promise in improving their walking ability in laboratory and controlled overground settings, it remains unknown whether these benefits translate to real-world environments, where they could have the greatest impact. This feasibility study demonstrates that an untethered ankle exoskeleton with an adaptable controller can improve spatiotemporal outcomes in eight individuals with CP after low-frequency exoskeleton-assisted gait training on real-world terrain. Comparing post-to pre-assessment, assisted walking speed increased by 11% and cadence by 7% (p = 0.003; p = 0.006), while unassisted walking speed increased by 8% and cadence by 5% (p = 0.009; p = 0.012). In the post-assessment, assisted walking speed increased by 9% and stride length by 8% relative to unassisted walking (p < 0.001; p < 0.001). Improvements in walking speed were more strongly associated with longer strides than higher cadence (R 2 = 0.92; R 2 = 0.68), suggesting that the exoskeleton may promote a more natural gait strategy. However, muscle activity outcomes, including co-contraction of the soleus and tibialis anterior, did not significantly change after training, potentially due to low-frequency and limited training sessions. These findings highlight the benefits of ankle exoskeletons in real-world settings and set the stage for future randomized controlled trials (RCTs) to evaluate their isolated effects on gait performance and neuromuscular outcomes in individuals with CP on real-world terrain.